(untitled) (International Journal of Engineering and Computer Science, 2014)
With the dynamic nature of Ad-hoc Networks coupled with the mobility of nodes results in breakage of the links due to ever changing topology of the nodes. When there is a substantial increase in the degree of mobility of the wireless network more link errors are likely to occur. When this happens, route repair is typically performed to establish a new route. Such route repair mechanisms suffers with the problems like high control overhead and long packet delay making them inefficient due to frequent failures of intermediate connections in an end-to-end communication. When there is a breakage in the intermediate link, it is favorable to discover a new route locally without resorting to an end-to-end route discovery. In this paper we propose ASRODV, an algorithm based on local route repair (LRR) mechanism such that the repair is confined to the vicinity of the broken link. The algorithm overcomes the limitations of standard AODV by decreasing the reaction time of recovery and the overhead of route maintenance. In the earlier AODV routing protocol, on the occurrence of a link break an error message is sent to the source stating that a link failure has taken place and further communication is stopped temporarily. Where as in ASRODV, nodes in the active path between source and destination act as a virtual source when link breakage occurs and there by the search process is continued till the link is formed to reach the original destination is reached. A comparison has been carried out between original routing protocol (AODV) and the improved algorithm (ASRODV) on various QOS parameters by simulating them in network simulator ns-2. The results demonstrate that the network performance can be significantly improved using the proposed local repair scheme.